KEARIFAN LOKAL DALAM LINGKUNGAN SEKOLAH DASAR SEBAGAI BENTENG ARUS NEGATIF MEDIA INFORMASI PADA SDIT DI BANJARMASIN - Marliza Noor Hayatie (Jurnal Ilmu Ekonomi dan Bisnis, 2020)
Education is an effort to develop students' potential in order to realize an atmosphere of learning and teaching and learning process to be active. Therefore, students can have spiritual strength, self-control, personality, intelligence, noble character, and the skills needed by the current environment. Education that utilizes local strengths in all aspects for the development of student competencies is a concept of education based on local wisdom. This research belongs to qualitative research. The population in this study was SDIT Anak Sholeh Mandiri, SDIT Al Firdaus, and SDIT Permata Jannati. Based on the results of research on strengthening the character of students with value-based local wisdom, it was found that to fortify the negative flow of information media through learning are: (1) The need for the application of local wisdom in an integrated Islamic elementary school environment, (2) Strengthening the character of students with local wisdom values is one of the efforts to prevent and overcome the negative flow of information media, (3) Students need to get learning about local wisdom in order to protect themselves from the negative flow of foreign culture.